Unravelling the genetic and epidemiological landscape of Handigodu syndrome in Southern India - Cicil Elsa Siby; Ismail Beary; Ranajit Das (Egyptian Journal of Medical Human Genetics)
Abstract Background Handigodu syndrome is a rare, progressive osteoarticular disorder endemic to the Malnad region of Karnataka, India. It predominantly affects the Chanangi and Chaluvadi communities in the Shivamogga and Chikkamagaluru districts. Initially attributed to environmental causes, the condition is now classified as a multifactorial disorder form of spondyloepi(meta)physeal dysplasia. Clinically, it manifests in three subtypes varying in severity and age of onset, primarily impairing the hip and spinal joints and significantly reducing mobility and quality of life. Despite its complex inheritance pattern, the disease is concentrated within socially isolated, endogamous groups with no evidence of inbreeding. This suggests that demographic history and population structure may play a significant role in its prevalence. Understanding the genetic basis and ancestral origins of Handigodu Syndrome is essential for improved diagnosis, genetic counselling, and potential therapeutic strategies. Results An integrated analysis of clinical, genetic, and epidemiological data from the Chanangi and Chaluvadi communities revealed a more complex inheritance model involving multiple loci with a strong founder effect. Whole-exome sequencing identified rare variants linked to cartilage and skeletal development. Genotype–phenotype correlations distinguished three clinical subtypes, and no environmental factors were associated, confirming a genetic cause. Conclusion This study confirms a genetic basis for Handigodu syndrome and provides compelling evidence for a founder mutation contributing to its prevalence within specific caste groups. The integration of genomic and demographic data reveals how population structure and isolation have shaped the inheritance of this disorder.